2007
DOI: 10.1103/physrevd.76.044008
|View full text |Cite
|
Sign up to set email alerts
|

Consistency off(R)=R2R02gravity with cosmological observations in the Palatini formalism

Abstract: In this work we study the dynamics of universe in f (R) = R 2 − R 2 0 modified gravity with Palatini formalism. We use data from recent observations as Supernova Type Ia (SNIa) Gold sample and Supernova Legacy Survey (SNLS) data, size of baryonic acoustic peak from Sloan Digital Sky Survey (SDSS), the position of the acoustic peak from the CMB observations and large scale structure formation (LSS) from the 2dFGRS survey to put constraint on the parameters of the model. To check the consistency of this action, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 110 publications
0
24
0
Order By: Relevance
“…In fact, these three OHRO at z = 1.43, 1.55 and 3.91 have been used to test many dark energy models, such as the ΛCDM model [44,53,54], the dark energy models with different EoS parameterizations [49,50], the generalized Chaplygin gas [55], the Λ(t)CDM model [56], the model-independent EoS of dark energy [57], the scalar-tensor quintessence [58], the f (R) = R 2 − R 2 0 model [59], the DGP braneworld model [60,61], the power-law parameterized quintessence model [62], and so on. It is found that the two OHRO at z = 1.43 and 1.55 can be easily accommodated in most dark energy models, whereas the OHRO at z = 3.91 can not, even in the ΛCDM model.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these three OHRO at z = 1.43, 1.55 and 3.91 have been used to test many dark energy models, such as the ΛCDM model [44,53,54], the dark energy models with different EoS parameterizations [49,50], the generalized Chaplygin gas [55], the Λ(t)CDM model [56], the model-independent EoS of dark energy [57], the scalar-tensor quintessence [58], the f (R) = R 2 − R 2 0 model [59], the DGP braneworld model [60,61], the power-law parameterized quintessence model [62], and so on. It is found that the two OHRO at z = 1.43 and 1.55 can be easily accommodated in most dark energy models, whereas the OHRO at z = 3.91 can not, even in the ΛCDM model.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests it worthwhile to seriously reconsider the cosmology of the Palatini-f (R) models. Expansionwise, they can generate a viable sequence of radiation dominated, matter dominated and accelerating era matching with the constraints, as has been shown for various parameterizations of the function f (R), most often with some power-law forms (with one, two or three * Electronic address: tomikoiv@pcu.helsinki.fi powers of R), but also with square-root, logarithmic and exponential forms for the curvature correction terms [26,27,28,29,30]. However, the inhomogeneous evolution present in any realistic universe has not been succesfully reconciled with observations in these models.…”
Section: Introductionmentioning
confidence: 99%
“…As is shown, this model is reproduced by (27) for small t when the curvature R is large, and by (31) or (33) when t is large. For a proper choice of the power α, the solution for large t is given by (31), which in combination with the solution (27) for small t, it looks like standard…”
Section: Reconstruction Of F (R)-gravitymentioning
confidence: 66%